Wolbachia Infection in Native Populations of the Invasive Tawny Crazy Ant Nylanderia fulva - Fernández, María Belén; Bleidorn, Christoph; Calcaterra, Luis Alberto (Frontiers in Insect Science, 2022)
Antagonistic interactions can affect population growth and dispersal of an invasive species. Wolbachia are intracellular endosymbiont bacteria that infect arthropod and nematode hosts and are able to manipulate reproduction, which in some cases leads to cocladogenesis. Moreover, the presence of the strictly maternally transferred Wolbachia in a population can indirectly induce selective sweeps on the hosts’ mitochondria. Ants have a Wolbachia infection rate of about 34%, which makes phylogenetic studies using mitochondrial markers vulnerable of being confounded by the effect of the endosymbiont. Nylanderia fulva is an invasive ant native to South America, considered a pest in the United States. Its distribution and biology are poorly known in its native range, and the taxonomic identity of this and its closely related species, Nylanderia pubens, has only recently been understood with the aid of molecular phylogenies. Aiming at estimating robust phylogenetic relationships of N. fulva in its native range, we investigated the presence and pattern of Wolbachia infection in populations of N. fulva from Argentina, part of its native range, to account for its possible effect on the host population structure. Using the ftsZ gene, 30 nests of N. fulva and four from sympatric Nylanderia species were screened for the presence of Wolbachia. We sequenced the MLST genes, the highly variable gene wsp, as well as glyQ, a novel target gene for which new primers were designed. Phylogeny of the ants was estimated using mtDNA (COI). We found supergroup A Wolbachia strains infecting 73% of N. fulva nests and two nests of Nylanderia sp. 1. Wolbachia phylogenetic tree inferred with MLST genes is partially congruent with the host phylogeny topology, with the exception of a lineage of strains shared by ants from different N. fulva clades. Furthermore, by comparing with Wolbachia sequences infecting other ants, we found that the strains infecting different N. fulva clades are not monophyletic. Our findings suggest there are three recent independent horizontally transmitted Wolbachia infections in N. fulva, and we found no evidence of influence of Wolbachia in the host mtDNA based phylogeny.